Corrosion Inhibition Of Mild Steel In 1 M Hcl Solution By Curcuma Longa Rhizome Extract - Kairi, Nurul Izni (2013)
The inhibitive action of the extract of Curcuma longa or generally known as turmeric for mild steel corrosion inhibitor in 1 M HCl solution was investigated. The effect of nine solvent systems (based on polarity) on the solubility of Curcuma longa has been studied. It was revealed that the Curcuma longa extracted with 95% aqueous ethanol gave the highest solubility and extraction yield. Characterization studies have been conducted to determine the curcumin content which is the active ingredient. Fourier transform infrared (FTIR) spectroscopy results suggest the presence of important functional groups that can fulfil the requirement as a potent organic corrosion inhibitor. The experimental findings based on the maximum absorption (λmax) of the Curcuma longa extract from the UV-Visible (UV-Vis) spectroscopy gives strong evidence on the presence of curcumin. The analysis of curcuminoids by means of reversed phase liquid chromatography mass spectrometry (LCMS) using C18 column have shown that curcumin, demethoxycurcumin (DMC) and bisdemethoxycurcumin (BDMC) were separated. The effect of Curcuma longa extract and standard curcumin as reference were investigated as corrosion inhibitors for mild steel in acidic media. The Curcuma longa extract exhibited 70% corrosion inhibition efficiency at 80 ppm concentration. Potentiodynamic polarization measurement revealed that the inhibitors behave as mixed type inhibitor, promoting retardation of both anodic and cathodic reactions. The electrochemical impedance spectroscopy (EIS) revealed that the charge transfer was the main controlling factor of the corrosion reaction. From the potential of zero charge (PZC) measurement, the negatively charged metal surface might be responsible for the electrostatic adsorption of the protonated molecules.